Development of Membrane-Active Honokiol/Magnolol Amphiphiles as Potent Antibacterial Agents against Methicillin-Resistant Staphylococcus aureus (MRSA) - Guo, Yong; Hou, Enhua; Wen, Tingyu; Yan, Xiaoting; Han, Meiyue; Bai, Li-Ping; Fu, Xiangjing; Liu, Jifeng; Qin, Shangshang (Journal of medicinal chemistry, 2021)
Currently, infections caused by drug-resistant bacteria have become a new challenge in anti-infective treatment, seriously endangering public health. In our continuous effort to develop new antimicrobials, a series of novel honokiol/magnolol amphiphiles were prepared by mimicking the chemical structures and antibacterial properties of cationic antimicrobial peptides. Among them, compound 5i showed excellent antibacterial activity against Gram-positive bacteria and clinical MRSA isolates (minimum inhibitory concentrations (MICs) = 0.5–2 μg/mL) with low hemolytic and cytotoxic activities and high membrane selectivity. Moreover, 5i exhibited rapid bactericidal properties, low resistance frequency, and good capabilities of disrupting bacterial biofilms. Mechanism studies revealed that 5i destroyed bacterial cell membranes, resulting in bacterial death. Additionally, 5i displayed high biosafety and potent in vivo anti-infective potency in a murine sepsis model. Our study indicates that these honokiol/magnolol amphiphiles shed light on developing novel antibacterial agents, and 5i is a potential antibacterial candidate for combating MRSA infections.